2015
DOI: 10.1016/j.jrurstud.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

How should rural policy be evaluated if it aims to foster community involvement in environmental management?

Abstract: This paper brings together different theoretical perspectives to propose an evaluation framework for policies which have the explicit aim to foster communities' involvement in the management of their natural environment in the context of sustainable rural development, such as the EU LEADER programme, Australia's Caring for Our Country, and UNESCO Biosphere Reserves. Previous policy evaluations have oversimplified the complex social-ecological systems on which these policies are intended to act, have lacked spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 68 publications
0
21
0
4
Order By: Relevance
“…Larcher et al [32] observed that for understanding the evolution of rural areas, participatory processes and civic engagement during decision making are essential. Using foster communities' involvement, Pranger et al [33] developed a framework to guide the evaluation of policy effectiveness in social-ecological systems and to manage the natural environment in sustainable rural development context. According to different authors, community involvement and public participation can be considered as vehicles to achieve sustainable environmental and development policy goals [34][35][36].…”
Section: The Best Practices Strategies Actions and Measures Appliedmentioning
confidence: 99%
“…Larcher et al [32] observed that for understanding the evolution of rural areas, participatory processes and civic engagement during decision making are essential. Using foster communities' involvement, Pranger et al [33] developed a framework to guide the evaluation of policy effectiveness in social-ecological systems and to manage the natural environment in sustainable rural development context. According to different authors, community involvement and public participation can be considered as vehicles to achieve sustainable environmental and development policy goals [34][35][36].…”
Section: The Best Practices Strategies Actions and Measures Appliedmentioning
confidence: 99%
“…In another study, Prager et al (2015) examined some aspects of the design and implementation of rural development project evaluation systems and identified a number of problematic issues. They found that many policies and lines of action had poorly defined and contradictory objectives, that there were difficulties in clearly defining the expected results of implementing this initiative, that measures overlapped due to their integrated, multisectoral approach, rendering it difficult to attribute causation and subsequent effect on a territory to any given measure, that there was still a need to determine the best time to conduct an evaluation, and that LAG managers rejected the idea of participating in self-evaluation processes that might reveal discrepancies in achieving objectives.…”
Section: Methodological Proposals For Evaluating Rural Development Prmentioning
confidence: 99%
“…Furthermore, it may not be feasible to adapt a common evaluation model to all rural development projects because the evaluation system must be consistent with the hierarchical level at which the evaluation is to be conducted (European, national, regional, district, or municipal). Accordingly, evaluations depend to a large extent on the previously established objectives, and these will differ according to the factors (level, perspective) that influenced methodology design (Prager, Nienaber, Neumann, & Phillips, 2015).…”
Section: Evaluation Of Eu Rural Development Programs and Leader Approachmentioning
confidence: 99%
“…Below we discuss each issue in turn. Monitoring and evaluation can apply to any level of initiative for environmental management – from project to programme or policy: our review encompasses all these, since these are often connected or conflated (Prager et al , ) but we focus particularly on the project‐level.…”
Section: Review Of Literature On Monitoring For Adaptive Managementmentioning
confidence: 99%